Pengaruh Jumlah Industri dan Tenaga Kerja Terhadap Nilai Produksi Industri Formal Kecil - Mu'tasim Billah; Mohammad Syaiful Pradana (Mathematics Department of Mathematics and Natural Sciences Unisda Lamongan, 2020)
The purpose of this study to analyze the effect of the number of industries and labor on the value of production in small industries in Lamongan Regency using the Durbin-Watson test. The Durbin-Watson test is an autocorrelation test that assesses the presence of autocorrelation in residuals. Data taken from the Central Bureau of Statistics of Lamongan Regency. Furthermore, it was analyzed using SPSS assistance. Based on the results of the analysis, it is known that there is no autocorrelation between the number of industries and workers on the value of production in small industries in Lamongan Regency.